Turismo e desenvolvimento sustentável na comunidade da Atalaia Nova no município de Barra dos Coqueiros/SE - Souza, Nara Vieira de (2007)
With the sprouting in the last years of necessarily defining the ambiental question as of the process of economic development, the tourism, being a new activity, generating impact in the global economy, comes being conceived in function of the most demanding sustainable parameters. In this universe the pertaining Nova Atalaia to the city of Barra dos Coqueiros/Sergipe, has been related to the tourist activity for the fact of that the place congregates natural aspects favorable, mainly the beaches, for the accomplishment of annual events, or still, to a flow of people, at some times, that they possess second residence in the localidade. However, the characteristics of the town are not with priority criteria for the evidence of providers actions of sustainable tourist place. In this way, the importance it object of this work consisted of identifying and to analyze the dynamics of the development of the tourism and its Inter-relations in the community of the Nova Atalaia, city of Barra dos Coqueiros-Sergipe.The research was constituted by samples of demands of local visitors (of events and swimmers) and by social actors.It is a qualitative work and a description-exploring study of the method of data s collection used was the survey, through half-structuralized interview and questionnaires. For analysis of the results software SPSS was used and first SWOT of the PDITS/SE, organized later in graphs, tables and texts. The research showed that, for some factors, it is impracticable to treat the Nova Atalaia without considering it now as practically new quarter of Aracaju what estimates an integration of city and state tourist politics, without losing of sight the approach of the peculiar characteristics of the Nova Atalaia. Another indicated result was that the activity of second residence does not demonstrate significant impact to be considered tourist aspect local. As a suggestion, the research points elements that could be transformed into attractive tourist and a necessary renewal of the paradigms until then followed by managers and local community